Effects of different particle-sized Al pastes on rear local contact formation and cell performance in passivated emitter rear cells. (September 2017) - Joonwichien, Supawan; Mochizuki, Toshimitsu; Shirasawa, Katsuhiko; Takato, Hidetaka
Abstract: This work presents the effects of different Al pastes on the rear contact formation in passivated emitter rear cells (PERC) after firing as well as the impact on cell performance. In this study, the rear side of PERC cells was metalized with two different PERC Al pastes—one consisting of fine particles, and another consisting of coarse particles. Our results found that the open-circuit voltages ( V oc ) are significantly higher for PERC cells using the Al paste with larger particles. Scanning electron microscopy (SEM) was used to analyze the local rear contacts. When metalized with the coarse particle Al paste, the local back surface field (local–BSF) was found to be several micrometers deeper. An SEM cross-sectional image revealed a non-uniform local–BSF when metalized with the fine-particle Al paste. Furthermore, the particle size of the Al paste used may also impact the adhesion and conductivity between the Al layer and the dielectric layers on the Si substrate.